An introduction to vector Gegenbauer processes with long memory. Issue 1 (28th August 2018) - Wu, Hao; Peiris, Shelton
Abstract : This paper introduces a flexible new class of time series models generated by the vector Gegenbauer autoregressive moving average structure. We establish existence and uniqueness of second order solutions under certain regularity conditions. Following a simulation study, we provide evidence that supports parsimonious properties of the model building and applications. © 2018 John Wiley & Sons, Ltd.